Influence of working environment on employee’s productivity: in comparisons between government agency and foreign firm / Nur Izzati Abdul Rahim and Norfadzlin Abu Bakar - Abdul Rahim, Nur Izzati; Abu Bakar, Norfadzlin (Faculty of Business and Management, 2014)
Workplace environment plays important roles towards employees’ productivity, behaviour, performance and working technique. Either towards negative or positive way, to some extent, workplace environment gives enormous impact to the employee itself. This research is focus on influences of workplace environment on employees’ productivity: in comparison between government agency and foreign firm. The first objective of this research is to investigate the level of employees’ productivity in comparison between government agency and foreign firm. Second objective is to determine the relationship between workplace environment and employees’ productivity. Last objective of this research is to determine the factors of workplace environment that significant to employees’ productivity. In order to analyse the result and see the comparison between these two sectors, all the objectives in this research were using different method. During this research, researchers have provided some recommendations and stated the significant of this study to the employees and employers to overcome the problem. The result of the findings is agreed temperature is the factor that most influences employees’ productivity in both organizations. Finally, the most important thing is cooperation between employees and employers that become main ingredient to make it all of this possible.